Calix[8]arene as New Platform for Cobalt‐Salen Complexes Immobilization and Use in Hydrolytic Kinetic Resolution of Epoxides. Issue 20 (25th September 2018) - Abdellah, Ibrahim; Martini, Cyril; Dos Santos, Amandine; Dragoe, Diana; Guérineau, Vincent; Huc, Vincent; Schulz, Emmanuelle
Abstract: Eight cobalt‐salen complexes have been covalently attached to a calix[8]arene platform through a flexible linker by a procedure employing Click chemistry. The corresponding well‐defined catalyst proved its efficiency in the hydrolytic kinetic resolution (HKR) of various epoxides through an operative bimetallic cooperative activation, demonstrating highly enhanced activity when compared to its monomeric analogue. As an insoluble complex, this multisite cobalt‐salen catalyst could be easily recovered and reused in successive catalytic runs. Products were isolated by a simple filtration with virtually no cobalt traces and without requiring a prior purification by flash chromatography. Abstract : Pass the filter, please ! A calix[8]arene supported cobalt‐salen complex has been straightforwardly prepared as multisite catalyst, efficient for the hydrolytic kinetic resolution of various epoxides, demonstrating highly enhanced activity compared to its monomeric analogue. It was recovered and re‐engaged in successive catalytic runs demonstrating its high stability. Products were isolated almost without any cobalt traces by simple filtration.